Iklim Kelas SMK Negeri se-Kecamatan Padang Timur - Novika, Asri; Marsidin, Sufyarma (Journal of Practice Learning and Educational Development, 2023)
This study aims to find out how the Class Climate of State Vocational Schools in East Padang District is viewed from the aspects of speed, cohesiveness, democracy, and the physical environment of the class. This research is quantitative descriptive. The research population was 961 students of Padang Timur District State Vocational School and a sample of 102 people using a proportional stratified random sampling technique. The data collection instrument was a Likert scale model questionnaire. The results of the study found that teacher perceptions in aspects 1) cohesiveness with an average score of 4.27, is in the good category, 2) speed with an average score of 4.19, is in the good category, 3) democracy with an average score of 3.94 is in the good category, 4) the physical environment of the class with an average score of 3.96 is in the good category. Thus it can be concluded that the Class Climate of State Vocational Schools in East Padang District is in the good category with an average score of 4.09. Based on these results, the authors suggest that the Class Climate of Public Vocational Schools in East Padang District can be maintained and needs to be improved again so as to create a conducive Class Climate.